SOLUTIONS OF HW4 MINGFENG ZHAO March 11, 2011 1. [Problem 3, in Page 55] Find the linear transformation which carries a. The points z = 0, 1, i into the points w = −1, −i, 0; b. The points z = −1, 1, i into the points w = 0, 3, ∞. Proof. a. Since w takes the points z = 0, 1, i into the points w = −1, −i, 0, then [z, 0, 1, i] = [w, −1, −i, 0], that is w + 1 −i + 0 z−0 1−i · = · z−i 1−0 w − 0 −i + 1 That is, we have z w + 1 −i · (1 − i) = · . z−i w 1−i So w+1 −i · w (1 − i)2 w + 1 −i · = w −2i w+1 = 2w Hence we have 2zw = (w + 1)(z − i) = (z − i)w + z − i, which implies that z z−i = w= z−i z+i b. Since w takes the points z = −1, 1, i into the points w = 0, 3, ∞, then [z, −1, 1, i] = [w, 0, 3, ∞], that is, z+1 1−i w−0 · = z−i 1+1 3−0 That is, we have z+1 w 2 2w = · = . z−i 3 1−i 3 − 3i So (z + 1)(3 − 3i) = 2(z − i)w. Hence w= z + 1 3 − 3i · . z−i 2 2. [Problem 5, in Page 55] Which linear transformations w = itself? az+b cz+d map the plane congruently onto Proof. Since w = az+b cz+d : C −→ C, then c = 0, and d 6= 0, that is, w = since w is a congruent map of the plane, so |a| = |d|. So all such maps are: w(z) = az + b, where |a| = 1. 1 a dz + db . On the other hand, 2 MINGFENG ZHAO 3. [Problem 6, in Page 55] What linear transformation corresponds to a rotation of the z-plane through 90◦ about the point z = 2? Proof. Let w be the linear transformation corresponds to a rotation of the z-plane through 90◦ about the point z = 2. So w has two fixed points 2 and ∞. So we have w = λ(z − 2) + 2 for some λ ∈ C. Figure 1. w(4) = 2 + 2i We consider z = 4, if we rotate z = 4 through 90◦ about the point z = 2, then we gt w(4) = 2 + 2i. So 2λ + 2 = 2 + 2i, that is, λ = i. Therefore, we have w = iz − 2i + 2. 4. [Problem 12, in Page 56] Determine the type of the following linear transformations: w= z , 2z − 1 w= 2z , 3z − 1 w= 3z − 4 , z−1 w= z . 2−z Proof. Let T (w) be the trace of w. z −iz a. If w = 2z−1 = −2iz+i , then T (w) = i − i = 0, so w is elliptic. b. If w = c. If w = d. If w = 2 √ z 2z 2i i 2 √ − √i2 = √i2 , so w is loxodromic. 3 1 , then T (w) = √ 3z−1 = √ − 2 i 2 i 2 3z−4 z−1 , then T (w) = 3 − 1 = 2, so w is parabolic. z √ z 2 = , then T (w) = √12 + √22 = √32 > 2, so w is hyperbolic. z √ 2−z − 2 + √22 5. [Problem 13, in Page 56] Show that every involutory linear transformation is elliptic. Proof. Let w(z) = az+b cz+d , and ad − bc = 1, and w(w(z)) = z, w(z) 6≡ z, then z = = = a· c· az+b cz+d az+b cz+d +b +d a2 z + ab + bcz + bd acz + bc + cdz + d2 (a2 + bc)z + ab + bd (ac + cd)z + bc + d2 SOLUTIONS OF HW4 3 So we have ac + cd = ab + bd = 0, a2 + bc = bc + d2 . If c = 0, then a2 = d2 . Since ad − bc = 1, so ad = 1, that is, a = d = 1 or a = d = −1. Since ab + bd = 0, so b = 0. Hence w(z) = z or w(z) = −z. Therefore w(z) = z. So w is elliptic. If c 6= 0, then a + d = 0, so w is elliptic. Therefore, w is elliptic. 6. [Problem 4, in Page 75] Show that the real and imaginary parts of the function ez satisfy both the Cauchy-Riemann equations and Laplace’s equation. Proof. Since w(z) = ez = ex+iy = ex cos y + iex sin y = u(x, y) + iv(x, y), so we have ux (x, y) = ex cos y uy (x, y) = −ex sin y vx (x, y) = ex sin y vy (x, y) = ex cos y. Hence ux = vy , and uy = −vx , that is, u, v satisfy the Cauchy-Riemann equations. So ∆u = uxx + uyy = vxy − vxy = 0, and ∆v = −uxy + uxy = 0, that is, u, v satisfy the Laplace’s equation. 7. [Problem 9, in Page 75] Determine which curves in the w-plane correspond to straight lines in the z-plane under the mapping w = ez , and which curves in the z-plane correspond to straight lines in the w-plane under the mapping. Proof. a. Case I: x = a for some a ∈ R, then w(x, y) = ea+iy = ea (cos y + i sin y) Figure 2. w(x, y) = ea (cos y + i sin y) which is a circle whose center is 0, and radius is ea . Case II: y = kx + b for some k, b ∈ R, then w(x, y) = ex+i(kx+b) 4 MINGFENG ZHAO = ex (cos(kx + b) + i sin(kx + b)) If k = 0, which is a ray. Figure 3. w(x, y) = ex (cos b + i sin b) If k 6= 0, we get a spiral curve. Figure 4. w(x, y) = ex (cos(kx + b) + i sin(kx + b)) b. Conversely, if we want cos θu(x, y) + sin θv(x, y) = c for some θ, c ∈ R, then cos θex cos y + sin θex sin y = c c So we get cos θ cos y + sin θ sin y = ce−x , that is, cos(θ − y) = ce−x . So x = ln cos(θ−y) . 8. [Problem 10, in Page 75] Let z = z(τ ) 6= 0 be a continuous function of τ ∈ [α, β], and denote the curve z = z(τ ) by γ. Show that arg z has unique value at every point of γ, once a definite value for arg z at the point z(α) has been established and the curve is described in a continuous manner, starting at that point. SOLUTIONS OF HW4 5 Proof. Let τ (t) = (β − α)t + α, t ∈ [0, 1], then we consider w(t) = z(τ (t)) = γ(t), and w(t) 6= 0 for all t ∈ [0, 1], we can define w(t) v(t) = = x(t) + iy(t). |w(t)| Our problem becomes: If arg z(α) = θ0 , we want to find a unique continuous function θ : [0, 1] −→ ∞ such that θ(0) = θ0 , and eiθ(t) = v(t). Existence: Since v(t) is continuous on [0, 1, then v is uniformly continuous, that is, for any > 0 such that there exists δ > 0, whenever |t − t0 | < δ, we have |v(t) − v(t0 )| < . Take = 1, then there exists δ > 0 such that, whenever |t − t0 | < δ, we have |v(t) − v(t0 )| < 1. If k 6= 0, we get a spiral curve. Figure 5. |z − z 0 | < 1 Let n ≥ 1 such that n1 < δ. Define t0 = 0, t1 = n1 , · · · , tn = nn = 1. For any 0t ∈ [t0 , t1 ], we can let θ0 (t) = θ0 + arcsin Im e−iθ0 v(t) , so θ0 (t) is continuous at [t0 , t1 ], and θ0 (t0 ) = θ0 (0) = θ0 . And for any t ∈ [t1 , t2 ], we define θ1 (t) = θ0 (t1 ) + arcsin Im e−iθ(t1 ) v(t) , so θ1 (t) is continuous at [t1 , t2 ], and θ1 (θ0 (t1 )). By induction, for any t ∈ [tk−1 , tk ], we define θk (t) = θk−1 (tk−1 ) + arcsin Im e−iθk−1 (tk−1 ) v(t) , so θk (t) is continuous at [tk , tk+1 ]. Therefore, we can define θ(t) = θk (t), if t ∈ [tk , tk+1 ] Therefore, θ(t) is continuous on [0, 1], and θ(0) = θ0 (t0 ) = θ0 . Uniqueness: If we have two continuous functions f, g : [0, 1] −→ ∞ such that f (0) = g(0) = θ0 , and eif (t) = eig(t) = v(t). So we get h(t) = f (t) − g(t) is continuous, and h(t) = 2πk(t), k(t) ∈ Z for all t ∈ [0, 1]. So k(t) has to be constant. On the other hand, we know h(0) = f (0) − g(0) = θ0 − θ0 = 0. So h(t) = 0, i.e, f (t) ≡ g(t) for all t ∈ [0, 1]. Department of Mathematics, University of Connecticut, 196 Auditorium Road, Unit 3009, Storrs, CT 06269-3009 E-mail address: mingfeng.zhao@uconn.edu